2009
DOI: 10.1007/s10886-008-9584-2
|View full text |Cite
|
Sign up to set email alerts
|

Lichen Substances Prevent Lichens from Nutrient Deficiency

Abstract: The dibenzofuran usnic acid, a widespread cortical secondary metabolite produced by lichen-forming fungi, was shown to promote the intracellular uptake of Cu 2+ in two epiphytic lichens, Evernia mesomorpha and Ramalina menziesii, from acidic, nutrient-poor bark. Higher Cu 2+ uptake in the former, which produces the depside divaricatic acid in addition to usnic acid, suggests that this depside promotes Cu 2+ uptake. Since Cu 2+ is one of the rarest micronutrients, promotion of Cu 2+ uptake by lichen substances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…The dibenzofuran compound usnic acid was reported to facilitate the uptake of cations such as Cu 2? (Hauck et al 2009). Some lichen compounds were shown to exhibit antibacterial (Motohashi et al 2010;Paudel et al 2010), cytostatic (Bogo et al 2010;Millot et al 2009;Tokiwano et al 2009), and antiviral activities (Esimone et al 2009).…”
Section: Lichen Chemistrymentioning
confidence: 99%
“…The dibenzofuran compound usnic acid was reported to facilitate the uptake of cations such as Cu 2? (Hauck et al 2009). Some lichen compounds were shown to exhibit antibacterial (Motohashi et al 2010;Paudel et al 2010), cytostatic (Bogo et al 2010;Millot et al 2009;Tokiwano et al 2009), and antiviral activities (Esimone et al 2009).…”
Section: Lichen Chemistrymentioning
confidence: 99%
“…These roles include antimicrobial activity, allelopathy, antiherbivory, chelating of heavy metals, light screening, and other proposed functions not yet sufficiently supported by experimental evidence under laboratory conditions (Lawrey 1986;Pöykkö et al 2005;Latkowska et al 2006;Hauck et al 2009;Solhaug et al 2009). Secondary metabolites may be responsible for the ecological success of lichenization, allowing lichens frequently to be the dominant organisms in environments characterized by extreme ecological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, physodalic acid from Hypogymnia physdodes, increase the Fe 2+ uptake and decrease the uptake of Cu 2+ , Mn 2+ and Na + (Hauck andHuneck 2007, Hauck 2008). Dibenzofurane usnic acid and divaricatic acid were both found to increase the intracellular uptake of Cu 2+ in Evernia mesomorpha and Ramalina menziesii (Hauck et al 2009), but reduce the Mn 2+ uptake. Recently, UV spectroscopic studies and X-ray diffraction analyses showed that the complexation of metal ions with lichen substances is widespread Fahselt 2004, Hauck et al 2009).…”
Section: Discussionmentioning
confidence: 88%